Variation of Fruit Morphological Traits in Capsicum annuum L. germplasm collection from North Macedonia - Drvoshanova Biljana; Ivanovska Sonja; Jakulovska Mirjana; Popsimonova Gordana (Journal of Agricultural, Food and Environmental Sciences (JAFES), 2022)
The aim of this research was to evaluate the phenotypic divergence of 33 local pepper landraces from North Macedonia based on their quantitative and qualitative fruit traits. According to the vernacular names they belong to the longum group and are traditionally consumed mostly in technological maturity. The experiment was laid out in randomized block design in three replications in 2018. Six quantitative fruit traits were evaluated: fruit length, fruit width, fruit weight, fruit pedicel length, fruit wall thickness and number of locules, as well as several qualitative traits: colour at intermediate stage, colour at mature stage, fruit shape, shape at blossom end, cross-sectional corrugation, ripe fruit persistence – pedicel with fruit and pedicel with stem. The PCA analysis identified that two principal components explain more than 77% of the variability based on the quantitative fruit parameters. The cluster analysis classified the accessions in three clusters, where the third cluster grouped seven local landraces that had highest values for fruit width, fruit weight and pericarp thickness as major yield components. It can be concluded that the results obtained for the fruit variability in the investigated 33 local pepper landraces from North Macedonia provided valuable information about the diversity of the collection. Furthermore, the local landraces identified in cluster three can be considered as potential source for selection of preferred traits or for further utilization in development of recommendations for direct production in the rural areas.
Keywords: Capsicum; fruit traits; principal component analysis; cluster analysis